Network of cognitive, emotional, and pain perception factors linked to non-suicidal self-injury in Chinese adolescents - Wei Luo; Jingbo Gong; Han-yu Zhou; Juanjuan Guo; Jieyu Xiao; Chao Yan; Yuqi Chen (BMC Psychology)
Abstract Background The cognitive-emotional model posits that negative self-concepts and maladaptive emotional regulation are key factors contributing to Non-Suicidal Self-Injury (NSSI). The Benefits and Barriers Model suggests that in order to engage in NSSI, certain ‘barriers’ (e.g., physical pain) have to be overcome to access the potential ‘benefits’ of NSSI. However, the associations among pain perception, pain management, and a series of cognitive and emotional factors in the context of NSSI remain unclear. In this study, we employed a network approach to investigate the network structures of these factors related to NSSI thoughts and behaviors among Chinese adolescents. Additionally, we examined the group differences in network structure by level of depressive symptoms. Methods A sample of 2756 adolescents validly completed self-report questionnaires about their emotional experiences, self-cognition, pain perception, depression level and frequency of NSSI. Network analyses were used to examine the interrelationship between NSSI, emotional experiences, self-cognition and pain perception. A network comparison test was conducted between individuals with high (HDS) and low (LDS) levels of depressive symptoms, based on the depression subscale of the Depression Anxiety Stress Scales (DASS-21), using a cutoff score of > 9. Results Among the cognitive-emotional-pain factors network, cognitive (i.e., early maladaptive schemas), pain perception (i.e., tolerance for mental pain) as well as NSSI thoughts were the main factors most strongly associated with NSSI behavior. A network comparison test revealed that NSSI thoughts had significantly higher centrality in the HDS group’s network (p = .015, Bonferroni-corrected). Edge-wise difference tests indicated a negative association between pain endurance and NSSI thoughts in the HDS group, an association that was absent in the LDS group. Additionally, the relationship between pain endurance and pain management showed opposite directions across the two groups. However, none of these edge differences remained significant after applying the strict Bonferroni correction for multiple comparisons. Conclusions Our study supported the cognitive-emotional-pain theoretical hypothesis, and highlighted the pivotal role of cognitive and pain perception factors in adolescent NSSI behavior. Additionally, these findings underscored the importance of mental pain tolerance and NSSI thoughts in understanding NSSI in depressed adolescents, offering new perspectives for prevention strategies.